Analisis Kurikulum Pendidikan Agama Islam di Indonesia dan Thailand (Studi kebijakan Kurikulum 2013 dan Kurikulum 2008 di tingkat SMA) - Fauzan, Fauzan; Lateh, Ayup; Arifin, Fatkhul (EDUKASIA, 2019)
The Curriculum Analysis of Islamic Education in Indonesia and Thailand (The Study of Curriculum 2013 and Curriculum 2008 in senior high school level). This study aims to determine the concept of PAI in Curriculum 2013 in Indonesia and Curriculum 2008 in Thailand at high school level (SMA).This research is a qualitative research by the use of literature study approach. The results of the study that: a) The policy of Curriculum 2013 in Indonesia and Curriculum 2008 in Thailand refers to the law of national education system in each country. b) Both curricula share the graduate competence standards (SKL) in common, being pious and skilful person in life, c) The content standard of both curricula refers to (SKL) in Indonesia, it is derived to be the core competence standard (KI) and basic competence (KD) while Curriculum 2008, it is derived to be learning standard (SP) and basic competence (KD), d) The Process Standard in Curriculum 2013 is implemented though a scientific approach which consists of observing, questioning, associating, experimenting, and networking. Meanwhile, Curriculum 2008 is implemented in a student centred approach with consists of an integrated approach, thinking, creating knowledge and social, problem solving, learning from experience, direct practice, research, independent learning, and moral action. e) Assessment standard In Curriculum 2013, used was an authentic assessment which consist of assessment test (paper and pencil test), performance, project, and portfolio for all grades in all educational system level. However, Curriculum 2008 assessed by using personal communication assessment, performance assessment, authentic assessment, and portfolio for all grades in every national education system level.